Fungsi dan Keutamaan Aksareng Usadha dalam Struktur Kebudayaan Masyarakat Bali - Geria, Anak Agung Gde Alit (Manuskripta, 2023)
The Modre, revered as Balinese sacred scripts, holds significance within the Balinese community for the virtues (kottaman) attributed to its characters in the context of traditional Balinese medicine (usadha). Modre scripts excellence is a vital component in therapeutic practices, believed to possess mystical and supernatural powers. Various palm-leaf manuscripts, including Aji Saraswati, Usadha Tantri, and Tutur Swara Wyanjana, are associated with the virtues of Balinese characters, serving as instrumental tools in Balinese medicine. These characters, believed to be soul-saving (pangraksaning jiwa), harness energy potential within usadhi pranawa, transforming bijaksara or modre characters into yantras. Through medication initiation, facilitated by mantras and the healer's yoga, this process is detailed in manuscripts like Ruměksa ing Wěngi, Punggung Tiwas, and Wisik Warah. The alignment of the healer's pure mind with the supreme Balinese characters, mahottama, is integral in applying usadhi pranawa during treatment, akin to the essential alignment in the Sabda tan Mětu ceremony with sacred scripture. === Aksara Modre (suci) telah diyakini oleh masyarakat Bali karena keutamaan (kottaman) aksaranya yang bertalian dengan bidang usadha (pengobatan tradisional Bali). Keutamaan aksara Modre menjadi sarana penting dalam prosesi pengobatan atau penyembuhan penyakit karena diyakini memiliki kekuatan gaib atau mistik. Ada sejumlah lontar yang berkaitan dengan kottaman aksara Bali, seperti Aji Saraswati, Usadha Tantri, Tutur Swara Wyanjana, dan yang lainnya. Kottaman aksara Bali sebagai sarana usadha Bali dapat digunakan sebagai penyelamat jiwa (pangraksaning jiwa). Hal ini didukung oleh sejumlah lontar yang diyakinioleh masyarakat Bali seperti Ruměksa ing Wěngi, Punggung Tiwas, Wisik Warah. Konsep penyatuan antara pikiran suci sang balian dengan aksara Bali mahottama itu, sangat penting dilakukan ketika mengobati dengan usadhi pranawa. Hal ini identik dengan prosesi sabda tan mětu ketika menyatukan pikiran dengan sastra aji (aksara suci).